The Effect of Brand Experience on Brand Equity and Visit Intentions in Virtual Alfamind Store - Tiffani Alexia Hotama; Yokie Radnan Kristiyono (Indonesian Marketing Journal, 2022)
Over the past decade, the retail industry has made a systematic transition, with the advent of online and mobile shopping, reshaping consumer behavior and business models around the world. The COVID-19 pandemic has changed consumer behavior in interacting with stores, so consumers will prefer virtual stores. To provide comprehensive empirical evidence for this study, the authors will review literature relevant to brand experience, their brand equity and visit intentions. Therefore, in this study, we will find out whether there is a positive influence of brand experience on brand equity and visit intentions. This study uses quantitative methods. Data was taken using Google Form which was distributed to 50 people for the preliminary study and 200 respondents for the actual research. Data collection was done by using convenience sampling. The data obtained was processed using the SmartPls 3.0 application. The results of this study indicate that there is a positive influence between sensory and brand equity. There is no positive influence between behavior on brand equity. There is a positive influence between emotional on brand equity. There is a positive influence between intellectual and brand equity. There is no positive influence between sensory and visit intentions. There is no positive influence between behavior on visit intentions. There is a positive influence between emotional on visit intentions. There is no positive influence between intellectual and visit intentions. There is a positive influence of brand equity on visit intentions.